(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the results of the research on the change of chicks and the period of maturity are presented when mixed feed samples are included in the diet of broiler chicks in age categories. In this case, it was found that when feeding broiler chicks, the minimum amount of protein in the mixed feed is higher than 26%, and a sharp decrease in the amount of vitamins reduces the viability of chicks by 20%.